SARS-CoV-2 transmission during an indoor professional sporting event - Pauser, J.; Schwarz, C.; Morgan, J.; Jantsch, J.; Brem, M. (Scientific Reports, 2021)
Sporting events with spectators can present a risk during the COVID-19 pandemic of becoming potential superspreader events that can result in mass-infection amongst participants—both sportspeople and spectators alike. In order to prevent disease transmission, many professional sporting bodies have implemented detailed hygiene regulations. This report analyzes SARS-CoV-2 transmission during a professional sports event (2nd division professional basketball in Germany). Whilst social distancing in this context is not always possible, the rate of infection was significantly reduced by wearing face masks that cover the mouth and nose. There was no infection amongst individuals who continuously wore medical particle filter masks (Category KN95/FFP2 or higher) during this sporting event.